Microwave Drying of Palm Oil Mill Effluent - Khalid, Kaida; Soon, Evelyn Mee Lin; Chow, Kok Fei (Universiti Putra Malaysia Press, 1998)
This paper describes the treatment of palm oil mill effluent (POME) by using microwave drying. The study concentrated on the variation of the drying rate with respect to different initial mass and microwave power and the effect of silicon carbide (SiC) to enhance the drying. The initial mass of sample and energy level ranges from 20. - 50 g and 91 - 504 watt respectively. The experimental results show that under the microwave treatment the drying time required to reduce the amount of sample to 25% of its initial mass at power level of 504 watt was within 3.5 - 6.4 min. While with SiC and at the same power level the drying time was only 1.8 - 3.6 min. This time is almost one-third of the time taken by conventional drying. The experimental results clearly showed that microwave drying can be considered as an alternative technique for the POME treatment since it is efficient, quick and does not pollute the environment.